The great indoors: linking human rights and the built environment. Issue 2 (September 2016) - Gellers, Joshua C
Abstract : It is widely held that environmental rights are conceived as legal guarantees intended to protect individuals from environmental harms and improve the quality of the environment. However, thus far much of the scholarly attention paid to environmental rights has focused on their application to the natural environment. I argue that, in conjunction with international human rights regarding housing, health, and water and sanitation, environmental rights should apply to the built environment as well. Through an analysis of international law, case law and scientific evidence, I demonstrate that protecting indoor environmental quality (IEQ) is necessary to the full realization of health, housing, water and sanitation, and environmental rights. This argument has three important implications. First, it provides victims of indoor environmental harms with a rights-based mechanism for redressing their grievances. Second, it makes a strong case for the inclusion of green building development in efforts to protect environmental rights throughout the world. Third, by directing policymakers to specific, measurable steps that can be taken to protect environmental rights, it refutes the charge that such rights are too ambiguous to be successfully implemented.